Comparative analysis of nocturnal vertical plasma drift velocities inferred from ground-based ionosonde measurements of hmF2 and h′F. (January 2015) - Adebesin, B.O.; Adeniyi, J.O.; Adimula, I.A.; Oladipo, O.A.; Olawepo, A.O.; Reinisch, B.W.
Abstract: Variations in the evening/nighttime ionosonde vertical plasma drift velocities inferred from the time rate of change of both the base of the F-layer height (Vz(h′F) ) and height of the peak electron density (Vz(hmF2) ) from an equatorial station were compared for better description of the E×B drifts. For better interpretation, both results were compared with the Incoherent Scatter (IS) radar observations (Vz(ISR) ) which is taken to be the most accurate method of measuring drift, and therefore the data of reference level. An equinoctial maximum and June solstice minimum in post-sunset pre-reversal enhancement (PRE) was observed for Vz(hmF2), Vz(ISR), and Vz(h′F) . The percentage correlation between VzhmF2 and Vzh′F ranges within 55–70%. While PRE for Vz(hmF2) peaked at 19 LT for all seasons, Vz(h′F) peaked at 18 LT for September equinox and December solstice, and start earlier. The nighttime downward reversal peak magnitudes for Vz(hmF2) and Vz(h′F) are respectively within the range of −4 to −14 and −2 to −14 m/s; whereas Vz(ISR) ranges within −12 and −34 m/s; and the peak time was reached earlier with the ionosonde observations than for the ISR. The PRE peak magnitude for Vz(hmF2), Vz(h′F) and Vz(ISR) varies between 3–14, 2–14, and 4–14 m/s for the entire seasons. Our results revealed higher drift correlation coefficients in both Vz(hmF2) vs. Vz(ISR) (0.983) and Vz(h′F) vs. Vz(ISR) (0.833) relationships during the equinoxes between 16–20 LT, at which time the F-layer altitude is higher than the 300 km threshold value; and lower for solstice period (0.326 and 0.410 in similar order). A better linear relationship between Vz(hmF2) and Vz(h′F2) was observed during the reversal (19–21 LT) phase period. PRE velocity was shown to be seasonal and solar activity dependent. Both VzhmF2 and Vzh′F compares almost equally with the ISR measurement. However, the PRE peak magnitude for the drift inferred using h′F2 is closer to the corresponding ISR magnitude during the equinoxes; whereas the drift inferred from hmF2 best represent the ISR magnitude for solstices. We established that both VzhmF2 and Vzh′F are governed by the same mechanism at nighttime, and as such any of them can be used to infer vertical drift as long as the 300 km threshold value condition is considered, otherwise chemical correction may be required for the F-layer uplift. Highlights: Ionosonde drift inferred from both hmF2 and h′F at the same location were compared. Comparison of the two were also made with Jicamarca ISR observation as a reference parameter. We established that both VzhmF2 and Vzh′F are governed by the same mechanism at nighttime. Our results revealed higher drift correlation relationships during the equinoxes and lower for solstice period.